Modern Problems of Antibiotic Therapy in Ophthalmology and the Perspective Ways of Solution. Literature Review - V. O. Ponomarev; V. N. Kazaykin; O. P. Ponomarev (Oftalʹmologiâ)
To date, the problem of interaction between humans and the surrounding microbiome continues to grow in the human population, which is expressed in the so-called crisis of antibiotic resistance. Microorganisms, being pathogens of infectious diseases, no longer have guaranteed pharmacological barriers that can stop their reproduction, which means that they continue to claim thousands of lives every year. This phenomenon is associated with many reasons, such as the presence of mobile genetic elements in bacteria that perform the function of horizontal gene transfer, responsible for their resistance to antibiotics. Mutational microevolution changes in the genotype of a bacterial cell can lead to the development of uncontrolled polyresistance. Also, the combination of micro-and macroevolutionary changes in the external signs of the pathogen determines the system of factors of aggression, invasion, protection and adaptation. Other factors causing antibioticoresistance include overuse of antibiotics and self-nominations during periods of self-medication, antibiotics and medical staff in subclinical doses, too short treatment courses, and sometimes their function in the absence of indications for therapy, the extensive use of antibiotics in agriculture. A number of preventive measures that could significantly affect the crisis of antibiotic resistance are being actively worked out at the state level and include programs to reduce the free circulation of antibiotics, optimize therapeutic regimes, improve diagnostic measures for the verification of pathogens, prevent the spread of infections, optimize interaction between pharmaceutical companies and registration organizations, stimulate investment and public-private partnership, and of course the international initiative on systemic interaction. This paper examines the cause-and-effect relationships that can have a direct impact on the resolution of the crisis of antibiotic resistance, which can be traced in the historical context and up to the present time, as well as describes modern promising scientific and technical directions that can give humanity a new «Golden bullet» against pathogens, in particular the use of artificial fluorophores-quantum dots.